I am not a number - Dupuis, Jenny Kay; Kacer, Kathy, 1954-; Newland, Gillian (Toronto, ON : Second Story Press, 2016)
"A picture book based on a true story about a young First Nations girl who was sent to a residential school. When eight-year-old Irene is removed from her First Nations family to live in a residential school she is confused, frightened, and terribly homesick. She tries to remember who she is and where she came from despite the efforts of the nuns to force her to do otherwise. Based on the life of Jenny Kay Dupuis' own grandmother, I Am Not a Number brings a terrible part of Canada's history to light in a way that children can learn from and relate to"--
Keywords: Indigenous peoples -- Canada -- Juvenile fiction; Off-reservation boarding schools -- Canada -- Juvenile fiction; Indigenous peoples -- Canada -- Residential schools -- Juvenile fiction; Indigenous peoples -- Canada -- Juvenile fiction; Off-reservation boarding schools -- Canada -- Juvenile fiction; Indigenous peoples -- Canada -- Juvenile fiction; Indigenous peoples -- Canada -- Residential schools -- Juvenile fiction